Transhumanism and Human Rights Development - Smyczek, Sara (Hybris, 2019)
The development of genetic engineering, artificial intelligence and new technologies is a contemporary concern regarding its impacts on the idea of humanity and, particularly in law, on the idea of human rights. The aim of the paper is to formulate the conceptual scope of the post- humanitarian subject, which becomes an important contribution to the study of a wider problem, which is the question about the direction of development of human rights and freedoms in the era of posthumanitary. Through the analysis of theoretical views, the author attempts to establish a connection between the concept of a human nature and the idea of human rights in order to verify belonging to the human species as the main measure for choosing entities that are entitled to human rights and freedoms.